O lago encantado e o caminho da chuva: noções de corpo, cura e cosmologia no Médio Solimões. Um estudo antropológico em comunidades da RDS Amanã - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This dissertation presents an ethnography about healing practices in three communities of the Reserve of Sustainable Development Amana: Ubim, São Miguel do Cacau and Boa Vista do Calafate, belonging to the municipality of Maraa, AM. Such communities are classified as amazon tradicional populations, riverside inhabitants of the Amana lake region, situated between the Solimoes river and the low course of the Japura river. The riverside communities addressed in this work are characterized as practitioners of shifting agricultural, fishing, hunting for livehoods and extractivism. They have their origins linked to migrations occurring during the peak of the period of rubber in Brazil. Those responsible for the healing practices are the healing specialists or curators, which are classified as "pegadores ou puxadores de dismintidura", prayers, midwives and "sacacas". The central question consists of how such curators carry out their treatments in a context cosmological permeated of non-human beings, such as enchanted, treating the perception of the body for the riverside inhabitants as a central foundation to understand various ontologies involved in this universe. To analyze the healing practices in the Medium Solimoes it is also important to consider the high diversity of natural resources such as medicinal plants and parts of animals that are used for the production of homemade remedies, often associated with prayers and massages, procedures used by Lake Amanã curators to treat the diseases and disorders of the residents of this region.
Keywords: Ribeirinhos - Amazônia; Lago Amanã; Cosmologia; CIENCIAS HUMANAS: ANTROPOLOGIA